Business Law Study on Consumer Privacy Protection in The Online Ticketing Service of PT Indonesia Railways - Aprilia Susanti (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
The significant increase in online activities cannot be separated from the many active internet users who use mobile internet connections to carry out their daily life, one of which is for the convenience of making ticket reservations at PT Indonesian Railways (KAI). The reason of this exploration is to figure out research of the business law of consumer privacy in the online ticketing service of PT KAI. Data collection was carried out by means of a literature study of the relationship between laws and regulations in consumer protection and the position of PT KAI as business actors and customers as consumers who submit their personal data privacy. The results of the study indicate a study of business law that concludes the protection of consumer privacy in the online ticketing service of PT KAI, then actually PT KAI has been supervised by several institutions such as the Ministry of Communication and Information with periodic database reports and state formulations with the principles of justice and fairness. In addition, in more detail PT KAI is also bound by the existence of Law Number 11 of 2008 concerning Information and Electronic Transactions which has provided legal protection for the security of consumer electronic data from PT KAI from illegal access andalso Law Number 27 of 2022 concerning about the consumer privacy protection.